Expanding the SHOC2 mutation associated phenotype of noonan syndrome with loose anagen hair: Structural brain anomalies and myelofibrosis. Issue 10 (5th August 2013) - Gripp, Karen W.; Zand, Dina J.; Demmer, Laurie; Anderson, Carol E.; Dobyns, William B.; Zackai, Elaine H.; Denenberg, Elizabeth; Jenny, Kim; Stabley, Deborah L.; Sol‐Church, Katia
ABSTRACT Noonan syndrome is a heterogenous rasopathy typically presenting with short stature, characteristic facial features, cardiac abnormalities including pulmonic valve stenosis, ASD and hypertrophic cardiomyopathy (HCM), cryptorchidism, ectodermal abnormalities, and learning differences. The phenotype is variable, and limited genotype phenotype correlation exists with SOS1 mutations often associated with normal cognition and stature, RAF1 mutations entailing a high HCM risk, and certain PTPN11 mutations predisposing to juvenile myelomonocytic leukemia. The recently identified SHOC2 mutation (p.Ser2Gly) causes Noonan syndrome with loose anagen hair. We report five patients with this mutation. All had skin hyperpigmentation, sparse light colored hair, increased fine wrinkles, ligamentous laxity, developmental delay, and 4/4 had a structural cardiac anomaly. Hypotonia and macrocephaly occurred in 4/5 (80%); 3/5 (60%) had polyhydramnios, increased birth weight or required use of a feeding tube. Distinctive brain abnormalities included relative megalencephaly and enlarged subarachnoid spaces suggestive of benign external hydrocephalus, and a relatively small posterior fossa as indicated by a vertical tentorium. The combination of a large brain with a small posterior fossa likely resulted in the high rate of cerebellar tonsillar ectopia (3/4; 75%). Periventricular nodular heterotopia was seen in one patient with a thick and dysplastic corpus callosum. We report on the first hematologic neoplasm, myelofibrosis, in a 2‐year‐old patient with SHOC2 mutation. Myelofibrosis is exceedingly rare in children and young adults. The absence of a somatic JAK2 mutation, seen in the majority of patients with myelofibrosis, is noteworthy as it suggests that germline or somatic SHOC2 mutations are causally involved in myelofibrosis. © 2013 Wiley Periodicals, Inc.